The Elephant in the Room: Toward an Integrated, Feminist Analysis of Mass Murder - Yardley, Elizabeth (Violence against women, 2023)
This article argues for a new approach to making sense of mass murder, emphasizing the urgency of recognizing the proliferation and significance of misogyny and domestic violence among perpetrators of this type of homicide. It is vital that scholarship recognizes the political economy of neoliberal patriarchy and seeks to better understand how harmful subjectivity develops in this context. We propose a new multilevel framework for the analysis of mass murder and issue a call to action for a global program of independent qualitative research and activism to tackle its drivers, prevent further harm, and save lives.